Construção histórica do conceito de dignidade humana no Direito Brasileiro - Mendes, Bianca Berdine Martins (2018)
The idea of human dignity receives criticism for its ambiguity, vagueness and imprecision. Researches intending for a better semantic delimitation of this concept in Brazilian Law have, in general, a prescriptive approach, looking for fundaments that result in a more adequate interpretation of the human dignity principle in the light of democratic, egalitarian values, or in defense of fundamental rights. However, the studies seems to assume that the idea of human dignity only came to exist juridically in Brazil with the promulgation of Constitution of 1988, which listed it as one of the principles of Republic. With that, attempts of delimitation of human dignity in Brazil seek out in foreign thinkers, in a supposed evolution of this idea in the History of Western thought, and in historical general milestones, such as the end of II World War, the origins of the understanding of this concept, apparently transplanted in the Brazilian legal system only in 1988. Thus, there are no researches that seek to comprehend human dignity in its integrality, that are concerned with questioning the sources of this idea in its specific action in Brazilian Law, extending beyond the constitutional positivation in 1988. The originality of these concerns is quite plausible in the scenario of theoretical stagnation of the thematic field, which always seems to revolve around similar issues. These two factors - originality and theoretical stagnation - motivated the adoption of the exploratory research design, which will have a historical method and will analyze legislative, documentary and bibliography sources. The objective of the investigation is to enable the formulation of more specific problems and hypothesis to be developed in future researches. For this purpose, the work was divided into 6 stages. The introduction presented human dignity in contemporary Brazilian Law, contextualizing the problem and justifying the chosen object. The chapter 1 exposed the methodology of the research and its chosen structure, explaining the systematization of the subsequent chapters. In the chapter 2, it was made a historical contextualization of human dignity in Western thought. Chapters 3 and 4 described the results of the investigation of human dignity in Brazilian Law, in a context prior to 1988. Finally, in the conclusion, relevant topics were pointed for future studies.